Nb and B effect on mechanical properties of Ti-Al based intermetallic materials - Yener, Tuba; Erdogan, Azmi; Gok, Mustafa Sabri; Zeytin, Sakin; Gök, Mustafa Sabri; Erdoğan, Azmi (Pergamon-Elsevier Science Ltd, 2019)
Ti-TiAl3 in-situ composites containing different percentages of Nb and B were effectively produced from Ti, Al, Nb and B powders by electric current assisted sintering (ECAS) technique which is a powder metallurgy processing method. Samples are sintered for 90 s with 2000 A current. The effect of B and Nb on the hardness, fracture toughness and wear resistance of samples were studied. The microstructure properties of the sintered samples were analysed with scanning electron microscopes (SEM), the phases in the samples were determined with XRD and their hardness and fracture toughness values were measured with a Vickers hardness tester with a load of 0.98 N and 98 N respectively. The highest fracture toughness value has been obtained with wt %10 Nb addition as 5.23 MPa m(1/2), whereas the highest hardness was determined as 965 HV for wt%5 B reinforced in situ-Ti-TiAl3 composite. Best wear resistance was obtained in the 47.5Ti-47.5Al-5B sample. While Nb additive had a negatory effect on wear resistance, additive B had a positive effect on wear resistance.
Keywords: Ti-Al Based Intermetallics; Ecas (Electric Current Activated Sintering); Hardness; Fracture Toughness; Wear